Comparative Analysis of Coal Quality across Various Coal Basins in Sumatra: A Case Study of Calorific Value, Moisture Content, and Sulfur Content - Hanum, Farrah Hanum; Hapsauqi, Iqbal; Jamilatun, Siti; Nirmalasari, Jiran (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Indonesia and other countries have used coal as their main energy source for many years. Due to variances in coal formation, maturity, and geological history, each basin may have a range in coal quality. It houses unique coal basins—South Sumatra, Central Sumatra, Riau, and Aceh—each marked by distinct geological features. Variations in coal formation, maturity, and geological history contribute to quality differences. The analysis of coal quality plays a crucial role in determining its suitability for various applications, including power generation, industrial processes, and export purposes. This study focuses on the coal characteristics of Riau (Coal A), Bengkulu (Coal B), South Sumatra (Coal C), and Jambi (Coal D), evaluating parameters such as calorific value, moisture content, and sulfur content. Employing ASTM-based analysis methods, results reveal that Coal D exhibits the lowest sulfur but has a diminished calorific value, while Coal A boasts a higher calorific value but the highest total sulfur content. Understanding such distinctions is crucial for determining coal's suitability for diverse applications like power generation, industrial processes, and exports. Hopefully, this research could help in estimating the economic potential of these basins, identifying areas with higher-quality coal, and planning future exploration and development activities.